1984
DOI: 10.1007/bf00303144
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of the special circular muscle layer and of the interstitial cells of Cajal related to the plexus muscularis profundus of mouse intestinal muscle coat

Abstract: The morphogenesis of the special layer and the interstitial cells of Cajal (ICC) related to the plexus muscularis profundus (PMP) of mouse intestinal muscle coat has been studied in foetuses at term, neonates not yet fed, suckling animals, weaning animals and adult animals. In foetuses at term, the special layer is absent, but presumed myoblasts of this layer are recognized in the tela submucosa facing the developing circular layer. The ICC, too, are not differentiated and presumed ICC-blasts are tentatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1987
1987
2006
2006

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 6 publications
1
24
1
Order By: Relevance
“…Interestingly, the intensity of the labelling for the NK1r was at its maximum at 7 days of postnatal life, while that for SP reached the highest intensity in the adult age. TEM studies [85] have shown that ICC-DMP acquire the adult features during the first week of post-natal life and that their differentiative steps are temporally related to those of the nerve plexuses. The difference between the earliest ages and adulthood in the NK1r distribution on the ICC-DMP probably depends on a progressive membrane re-organization of the receptors in a cell that increases in size and changes in shape.…”
Section: Nk1r-ir Icc-dmp and Sp-ir Nerves During Gut Developmentmentioning
confidence: 99%
“…Interestingly, the intensity of the labelling for the NK1r was at its maximum at 7 days of postnatal life, while that for SP reached the highest intensity in the adult age. TEM studies [85] have shown that ICC-DMP acquire the adult features during the first week of post-natal life and that their differentiative steps are temporally related to those of the nerve plexuses. The difference between the earliest ages and adulthood in the NK1r distribution on the ICC-DMP probably depends on a progressive membrane re-organization of the receptors in a cell that increases in size and changes in shape.…”
Section: Nk1r-ir Icc-dmp and Sp-ir Nerves During Gut Developmentmentioning
confidence: 99%
“…Faussone-Pellegrini (1984) was more cautious, in that she also referred to these cells as ''ICC blast-like cells,'' which could not be identified with certainty. Torihashi and coworkers (Willenbucher et al, 1992;Torihashi et al, 1997) reported that such ICC blast cells were not observed at day 18 of gestation.…”
Section: Ontogenesis Of the Pacemaker Activity In Neonatal Mouse Smalmentioning
confidence: 99%
“…Cytodifferentiation of the interstitial cells of Cajal (ICC) from fetal to adult life has been studied only in the small intestine of the mouse [Faussone-Pellegrini, 1984. 1985a.…”
Section: Introductionmentioning
confidence: 99%